Program Sekolah Ramah Anak di Pos PAUD Sekar Tanjung Kota Semarang - Rifda Asysyifa Rihadatul ‘Aisy; Mu’arifuddin Mu’arifuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to describe the Child-Friendly School Program at the Sekar Tanjung Early Childhood Education Center in Semarang City, including its planning, implementation, and supporting and inhibiting factors. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research subjects consist of the school principal, educators, and parents as informants. Data analysis in this study uses an interactive analysis model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Child-Friendly School Program has been well-planned through the formation of an implementation team, socialization of children's rights, and the development of Child-Friendly School Program policies. This was achieved through planning in the form of child rights education, child involvement in learning, and the integration of Child-Friendly School Program principles into the daily learning implementation plan. The implementation of Child-Friendly School Program includes teacher understanding, educator training, the use of learning facilities, child participation, cooperation with parents and external parties, and protection against violence. Supporting factors include the commitment of school principals and teachers, management of facilities and infrastructure, parent participation, and support from the education office. The inhibiting factors are limited human resources and facilities and infrastructure, which still require further development.